Review paper on Assessing of depression by Beck Depression Inventory (BDI) - Shahlaei, Leili; Hasan, Shahizan; Samsudin, Mohd Ali; Kiumarsi, Shayan; Mohd Yusoff, Azlina (School of Social Science, 2015)
The study aimed at investigating the impact of depression on mental health and assessing this disease by Beck Depression Inventory (BDI). Depression is the significant mental disorder that has effect on quality of life and it is one of the main reasons for death in the world. Assessing depression can have an important role to play .The study discusses about measurement that is such an important issue needs to receive a great deal of attention in order to create grounds to be prevented or cured. This tool is appropriate for the study because it allows the reader to understand how to measure and identify symptoms of depression. One of the recommendations of the paper is that the tool should be carefully applied in order to improve mental health and reduce the prevalence of depression.